PENGARUH FESES KAMBING DAN KONSENTRASI URIN KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica rapa L. ) DALAM POLIBAG - Dominggo De Ornay, Marianno; Sunaryo, Yacobus; Arnanto, Driska (JURNAL ILMIAH AGROUST, 2025)
This research aims to determine the interaction between goat feces and goat urine concentration on the growth and yield of green mustard plants. The research was carried out in a yard located in Berbah, Seleman, Yogyakarta, Special Region of Yogyakarta. This research was conducted using the Complete Randomized Block Design (RAKL) method with two treatment factors. The first factor is goat feces and secant charcoal in the composition of the planting media consisting of three levels. The second factor is the goat urine concentration treatment, consisting of three levels. Data were analyzed using variance at the 5% level followed by using Duncan's Multiple Range Test (DMRT) at the 5% level. The variables observed include plant height, number of leaves, leaf length, leaf width, fresh weight, dry weight. The research results showed that the interaction between goat urine concentration and the composition of the planting medium had a significant effect on plant height, number of leaves, leaf width, leaf length, fresh weight and dry weight on the growth and yield of mustard greens. The planting media treatment showed significant differences in all variables of growth and yield of green mustard plants.